Concrete Repair Using Fiber from Surgical Mask - Mazlan, Muhamad Arif Shafiq; Ayop, Sallehuddin Shah (Journal of Structural Monitoring and Built Environment, 2023)
In this new Norma, surgical mask was a thing that important to wear in public. Because of the frequent use of surgical mask, the huge of waste of surgical mask were disposed per day. The surgical mask was made from a polypropylene fiber that widely used in construction in the term of concrete fiber. Polypropylene fiber had their own credibility to provide the ductile strength for concrete to reduce the cracking of concrete that was a brittle material. To study the effectiveness of the fiber from surgical mask, this fiber was used as concrete repaired materials The material of concrete repair was the important things to provide or improved the deteriorated concrete. Therefore, this study will determine that fiber from surgical mask can be used as a concrete repaired material through the comparison of flexural strength between the controlled concrete and repaired concrete. Three methods of concrete repaired was tested in this study, single layer polypropylene fiber, single layer surgical mask fiber, and double layer surgical mask fiber. Those method was applied to deteriorated concrete prism. The result for flexural strength of concrete after repaired for all method was decreasing from the strength before repaired but the result of second method was higher than the first method and the third method was higher than the second method. The concrete failure condition, showed the failure happened on the same location failure before repaired that meant the failure happened on the concrete repaired material. However, the used of surgical mask fiber was changed failure condition of the concrete prism from sudden failure to periodic failures. Therefore, the surgical mask was effective to repair the damage concrete due to crack failure because the fiber of the surgical mask can controlled that crack.